A study on students' perspective on factors leading to anxiety: a comparison between two proficiency levels / Suhaila Muhamad - Muhamad, Suhaila (2009)
Anxiety has been identified by many as one of the affective domains that tamper with the learning of a Second Language. The factors leading to anxiety have been identified by numerous researchers of the past, most of which are accompanied with debilitative effects towards the language learning experienced by the learners. In this study, the factors leading to anxiety among the learners were investigated. In the past, communication apprehension, fear of negative evaluation and test anxiety had been named the most influential aspects in an English classroom that can contribute to the learners' apprehension, thus tampering with their language learning process (Horwitz etal, 1986). For the purpose of this study, the factors suggested by Horwitz et.al (1986) were taken into consideration. In addition to that, the learners' perspectives on the matter were also taken into consideration. The study involved learners from two different proficiency levels - the highest and the lowest - and both quantitative and qualitative qualities were used for the data collection. Overall, 90 learners participated in the first part of data collection, which involved the use of SLCAS (Second Language Classroom Anxiety Scale), adapted from Horwitz et.al's (1986) Foreign Language Classroom Anxiety Scale, and a total of eight were chosen for the interview. The data retrieved revealed that while the factors forwarded by Horwitz et.al (1986) were among the factors that lead to anxiety in the language classroom, the learners found teacher role to also be a contributing factor to their apprehensiveness in the language classroom. The study also revealed that while learners did feel the effects of anxiety in their language classroom, the apprehensiveness proved to be facilitative rather than debilitative, as the hurdles they faced were overcame, and used to be a push factor that helped boost their language learning process. As a mean to ease their apprehensiveness in the classroom, the learners maintained their need to feel a sense of community and the freedom to speak in the language classroom, with more group work and classroom discussions infused throughout their learning process.